Analisis Budaya Organisasi pada Universitas Muhammadyah Lampung dengan Menggunakan Model Denison - . Marzuki (Universitas Bandar Lampung (UBL), 2014)
The failure of a organsisasi / company mainly due to failures in managing the corporate culture. The management of organizational culture can not be separated from the role of organizational leadership. With the able leadership of a figure for their subordinates, will be able to raise morale so that his subordinates would perform jobs more effectively and efficiently, thereby producing a good performance. What research problem is cultural portrait on the organization Muhammadiyah University of Lampung?. Based on the discussion and interpretation of the study authors conclude it can be sebabagai following few things: 1) the cultural characteristics involvement (involvement) in the UML organization evaluated by this research respondents in both categories. 2) the cultural characteristics of consistency (consistency) in UML organization evaluated by this research respondents in the category good enough. 3) Cultural adaptability characteristics (adaptability) in UML organization judged by the respondents of this research in a category quite well. 4) Feature Cultural Mission (Mission) in UML organization assessed by the respondents of this research in the category good enough. 5 In the vision indicators, respondents were inii rate or fairly good. Characteristics Cultural Organization Muhammadiyah University of Lampung is a flexible organization but rather focus on the internal environment.Kegagalan suatu organsisasi/perusahaan terutama disebabkan kegagalan dalam mengelola budaya perusahaan. Pengelolaan budaya organisasi tidak terlepas dari peran pimpinan organisasi. Dengan kepemimpinan yang mampu menjadi figur bagi para bawahan, akan dapat membangkitkan semangat kerja sehingga para bawahannya akan melakukan pekerjaan-pekerjaan lebih efektif dan efisien, dengan demikian akan menghasilkan kinerja yang baik. Masalah penelitian adalah Bagaimana potret budaya organisasi pada Universitas Muhammadiyah Lampung ?. Berdasarkan pembahasan dan interpretasi penelitian maka dapat penulis simpulkan beberapa hal sebabagai berikut: 1) Ciri budaya keterlibatan (involvement) pada organisasi UML dinilai oleh responden penelitian ini dalam katagori baik. 2) Ciri budaya konsistensi (consistency) pada organisasi UML dinilai oleh responden penelitian ini dalam kategori cukup baik. 3) Ciri Budaya kemampuan beradaptasi (Adaptability) pada organisasi UML dinilai oleh responden penelitian ini dalam katagori cukup baik. 4) Ciri Budaya Misi (Mission) pada organisasi UML dinilai oleh responden penelitian ini dalam katagori cukup baik. 5 Dalam indikator visi, responden penelitian inii menilai sedang atau cukup baik. Karakteristik Budaya Organisasi Universitas Muhammadyah Lampung merupakan organisasi yang fleksibel namun lebih fokus pada lingkungan internal.